2018
DOI: 10.1002/jbm.b.34297
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term marginal adaptation and nanoleakage of class V cavity restored with organic filler filled 4‐META/MMA‐TBB resin

Abstract: The current restorative materials used for cervical lesions restoration still need to be improved. A low E-modulus restorative material Bondfill SB (group BF) is developed. This study was to evaluate marginal adaptation and nanoleakage expression at dentin bonding interface of BF before and after artificial aging cycling when used for class V cavity restoration in vitro. Cavities were prepared in human premolars and restored with either Bondfill SB or Z100 (group SZ). Quantitative data were analyzed by t-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previously, our group mixed naHAp and SB and demonstrated that 10% naHAp/SB and 30% naHAp/SB exhibited the same level of tensile strength as SB. 28 SB exhibited the long-term success of cervical root lesions restoration because of strong adhesion to dentin 31 and naHAp/SB could keep its tensile strength after the thermal stressing which was repeated for 5000 cycles. 28 On F I G U R E 1 Effects of naHAp/SB on cell adhesion and proliferation of HPDLSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group mixed naHAp and SB and demonstrated that 10% naHAp/SB and 30% naHAp/SB exhibited the same level of tensile strength as SB. 28 SB exhibited the long-term success of cervical root lesions restoration because of strong adhesion to dentin 31 and naHAp/SB could keep its tensile strength after the thermal stressing which was repeated for 5000 cycles. 28 On F I G U R E 1 Effects of naHAp/SB on cell adhesion and proliferation of HPDLSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SB contains the acidic functional monomer, which is 4-Methacryloxyethyl trimellitate anhydride (4-META) that can bond to tooth structure [30]. The 4-META/MMA-tri-n-butylborane (TBB) resin formulation of the SB was shown to durably bond to enamel and dentin, especially to deep and cervical dentin, this, in part, owing to its high degree of polymerization in a wet dentin environment compared with other resin-based cements [31]. However, Superbond and Superbond C&B (Sun Medical) were documented with a bond strength that decreased upon 6 months of water-storage aging [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that to achieve a successful restoration at longterm relies on durable marginal integrity of the restoration ( 48 ). Leakage and bacterial migration from the restoration interface can cause a series of problem such as post-operative hypersensitivity, secondary caries and eventually failure of the restoration ( 49 ). In the present study building a wellsealed restoration was the main goal at every stage of the study.…”
Section: Discussionmentioning
confidence: 99%